PERAN SERTA MASYARAKAT DALAM PELESTARIAN HUTAN MANGROVE DI DESA BATU GAJAH KABUPATEN NATUNA - yas, Il; Lumangkun, Augustine; Natalina H, Uke (Universitas Tanjungpura, 2013)
This research aims to determine the role of the community in preserving the existence of mangrove forest sand the relationship of individual factors with public participation in mangrove forest conservation in the village of Batu Gajah. The samples are taken 75KK of 267KK. Data processing is using ChiSquare test. Research shows that community participation was medium because of them just want to get incentives from conservation activitiesandany divergence views on planting location. The individual factors such as age, income, and long lived perception has no real relation. While education and knowledge factors showed an association with public participation in mangrove forest conservation in the village of BatuGajah. Keyword:participation, community, conservation, mangrove.